Perancangan Majalengka Bilingual Boarding School Sebagai Sekolah Satuan Pendidikan Kerja Sama (SPK) di Kabupaten Majalengka dengan Pendekatan Konsep Eco-Tech Architecture - Lala Dena Hermawati; Purnama Sakhrial Pradini (DPPM Universitas Pelita Bangsa, 2022)
The competitive globalization era demands the availability of quality natural resources. The development of Science and Technology grow so fast in line with the international competition. Nowadays, the prediction of infrastructure coonstruction acceleration in Majalengka District will increase the growth of the industrial sector with international standard facilities. This phenomenon demands adaptation of local people to increase their human resources qualities whose smart in order to master the science and technology, to compete in internatonal scale, to absorb in industrial sector, and to empower in social economic. Therefore, the education condition in Majalengka District must be fixed soon because the strengthening in education sector will determine the growth of the area. One of the effort is to organize the boarding school applied school Satuan Pendidikan Kerja Sama (SPK) system to realize the smart people, compete in internatonal scale, and able to answer the worries which is caused by background diversity, culture, religion, sociall status, economic, origin, and negative influence of the other globalilzation. According to the phenomena, so, the planning of majalengka’s bilingual boarding school as school Satuan Pendidikan Kerja Sama (SPK) in Majalengka District must be organized. As for approach of Eco-Tech Architecture concept on this planning is one of the effort to support commitment on Indonesia’s sustainable development to particapate at global world and to implement the environmentally friendly development in Majalengka District. Keywords : Majalengka District, Boarding School, SPK, Eco-Tech Arhcitecture